Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300732
|View full text |Cite
|
Sign up to set email alerts
|

Together in Bed?

Abstract: In this paper, we investigate the use of mobile technology in an underexplored context, the bed that couples share. Despite large amounts of research on the impact of pre-bedtime technology use on our sleep and mental state, scant research in the HCI field focuses on the physical bed as a negotiated site of technology use by couples. This paper explores (a) the meaning of the bed accessed by mobile technology and (b) the strategies of both individual and shared technology use in bed, in the context of couple's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Our study gives a unique glimpse into the typical and ideal bedtime routines of American couples. Building on prior work showing that individuals engage with phones and other technologies at bedtime (Exelmans & Van den Bulck, 2016; Gradisar et al, 2013; Salmela et al, 2019), we examined, through the coding of narratives, whether technology use (both shared and apart) was occurring in individuals’ typical and ideal bedtime routines. The overall tone of these ideal and typical bedtime routine descriptions supports prior work suggesting that a partner’s technology use, particularly problematic use, has the potential to negatively affect relationships (McDaniel, Malan, & Locher, 2018; Morgan et al, 2017; Spencer et al, 2019); however, the mere occurrence of apart technology use in typical bedtime was not associated with worse satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study gives a unique glimpse into the typical and ideal bedtime routines of American couples. Building on prior work showing that individuals engage with phones and other technologies at bedtime (Exelmans & Van den Bulck, 2016; Gradisar et al, 2013; Salmela et al, 2019), we examined, through the coding of narratives, whether technology use (both shared and apart) was occurring in individuals’ typical and ideal bedtime routines. The overall tone of these ideal and typical bedtime routine descriptions supports prior work suggesting that a partner’s technology use, particularly problematic use, has the potential to negatively affect relationships (McDaniel, Malan, & Locher, 2018; Morgan et al, 2017; Spencer et al, 2019); however, the mere occurrence of apart technology use in typical bedtime was not associated with worse satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Sleep Foundation’s 2011 Sleep in America poll, 9 of 10 Americans use technology in the hour before bedtime, with most using televisions (Gradisar et al, 2013). Additionally, in an interview and survey study by Salmela et al (2019), most couples reported routinely bringing their smartphones to bed and engaging in individual technology use for a short time before falling asleep, especially after the other partner was already sleeping. This trend is not limited to only American adults.…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of co-located couples according to related work, and perhaps our own everyday life experiences, technology can be invading in a relationship, leading to dissatisfaction, or even conflict when its design and use is relevant only for one partner, instead of the couple as a whole [39,50,52]. For example, when someone is interacting with their phone, this might be perceived as intrusive by their partner [25,39,42,50].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of co-located couples though, which is the focus of this paper, technology does not always have a positive effect. Often, technology can interfere, bring frustration, or even damage romantic relationships when its use is not relevant for both partners [25,39,42,50,52]. But in the cases where technology is specifically designed for mediating intimacy for co-located couples, research findings look more promising.…”
Section: Introductionmentioning
confidence: 99%
“…at the dinner table or after bedtime. Looking at adult couples rather than teens, Salmela et al [22] highlight that phone use in bed is widespread, and that it not only disrupted sleep patterns but that it also affected the attention given to partners and intimate interactions.…”
Section: Engaging Teens With Sleepmentioning
confidence: 99%